Design of a temperature control system to increase profits in the noodle drying process - Uchofen Ayala, Estrella Del Carmen; Sánchez Pérez, Joselito; Arroyo Ulloa, Maximiliano (LACCEI, 2025)
The purpose of this research was to design a temperature control system to increase profits in the noodle drying process. The company under study produces a variety of products such as fine, thick and ribbon noodles. However, the drying process presents problems due to non-uniform distribution of hot air, which generates moisture levels outside the quality parameters and causes reprocessing. To address this problem, we began with a diagnosis of the process, identifying causes and evaluating reprocessing percentages by means of statistical sampling. The current dryer was modeled in SolidWorks and the economic impact of rework was calculated. Subsequently, the design of a new temperature control system was developed to determine the optimum drying time, a PID controller programmed in MATLAB was implemented, the control plane was designed in Cade Simu and the control system was simulated in SoMachine. Finally, a cost-benefit analysis was performed, which showed an improvement by reducing the percentage of shredded noodles to 10 % and of wet noodles to 12 %. Finally, the improvement made it possible to achieve an annual profit in the first year of S/ 991 876 and a cost benefit of 2,91, which showed that the project was viable and profitable.